New insights into the germline genes and CDR3 repertoire of the TCRβ chain in Chiroptera - Zhou, Hao; Li, Jun; Zhou, Dewei; Wu, Yingjie; Wang, Xingliang; Zhou, Jiang; Ma, Qingqing; Yao, Xinsheng; Ma, Long (Frontiers in Immunology, 2023)
Bats are natural reservoirs of many viruses, but their unique immune system allows them to co-exist with viruses and rarely manifest disease. Our understanding of the bat adaptive immune system is limited due to no database or tool that can process TCR High-throughput sequencing (HTS) data for bats and considerable diversity of the Chiroptera category. To explore our understanding of bats’ t-cell immune system, we established a reference library of TCR-β germline genes based on the annotation of Rhinolophus ferrumequinum (Greater Horseshoe Bat, Rhinolophidae) (RF), Phyllostomus discolor (Pale spear-nosed bat, Phyllostomidae) (PD) and Pipistrellus pipistrellus (Common pipistrelle, Vespertilionidae) (PP). Further, we analyzed the Rhinolophus affinis (Intermediate horseshoe bat, Rhinolophidae) (RA) TCR-β repertoire by HTS. The bats’ TCR-β repertoire was formed by rearranging the V-D-J-C genes with a D-J/V-D deletion and insertion, showing a high diversity; the conserved amino acids suggest that bats’ T-cell recognition of antigens is MHC-restricted. The sequencing and analysis processes of immune repertoire established in this study can apply to the research of adaptive immune systems in bats and novel species.